Efficacy and Safety of Percutaneous Pulmonary Artery Subtotal Occlusion and Chronic Total Occlusion Intervention in Chronic Thromboembolic Pulmonary Hypertension. (16th July 2021) - Gerges, Christian; Friewald, Richard; Gerges, Mario; Shafran, Inbal; Sadushi-Koliçi, Roela; Skoro-Sajer, Nika; Moser, Bernhard; Taghavi, Shahrokh; Klepetko, Walter; Lang, Irene M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Balloon pulmonary angioplasty (BPA) is an emerging percutaneous therapy for patients with inoperable chronic thromboembolic pulmonary hypertension, and patients with mean pulmonary artery pressure ≤30 mm Hg have an excellent survival. Common vascular lesion types are ring-like stenoses (type A), web lesions (type B), subtotal occlusions (type C), chronic total occlusions (CTOs; type D), and tortuous lesions (type E). Occlusive lesions (ie, subtotal occlusions and CTOs) are the most challenging. Risk and benefit of pulmonary occlusive lesion intervention in chronic thromboembolic pulmonary hypertension has not been studied. We evaluated the impact of percutaneous pulmonary artery subtotal occlusion and CTO intervention on BPA treatment response. Methods: One hundred twenty patients underwent 712 BPA procedures between April 2014 and October 2019 at the Medical University of Vienna. Clinical features and hemodynamics were assessed at baseline and 6 to 12 months after the last BPA session. Results: A total of 2542 lesions were targeted: 720 occlusions (28.3%; 352 CTOs and 368 subtotal occlusions) and 1822 nonocclusion lesions (71.7%). Complications occurred in 6.0% of all procedures (severe complications in 0.4% of all procedures). The overall success rate for recanalization of occlusions was 81% (subtotal occlusions [type C lesions], 98%; CTOs [type D lesions], 50%). Number of successfully treated lesions of any type (β, −0.86 [−1.19 to −0.53]; P <0.001), number of successfully treated occlusions (β, −2.17 [−3.38 to −0.97]; P =0.001), and number of successfully treated nonocclusion lesions (β, −0.81 [−1.25 to −0.37]; P <0.001) emerged as predictors of relative change in the mean pulmonary artery pressure. The impact on relative change in the mean pulmonary artery pressure was higher for CTOs (β, −5.88 [−10.49 to −1.26]; P =0.014) than for subtotal occlusions (β, −2.51 [−4.18 to −0.83]; P =0.004). Conclusions: The number of successfully treated vascular lesions predicts treatment response to BPA. The number of successfully recanalized occlusions (particularly CTOs) appears to have the strongest impact on change in mean pulmonary artery pressure, highlighting the importance of advanced BPA technique.